Mucormycosis in RT-PCR negative Covid 19 patient with newly diagnosed Diabetes Mellitus: A Case Report - Sagar, Vankadari Venkata Sesha Satya; Yelne, Pallavi; Mathurkar, Swapneel; Gaidhane, Shilpa (Asian Journal of Medical Sciences, 2021)
Corona Virus Disease 2019 (COVID 19) is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), first identified in Wuhan city of China in December 2019. Since then, the disease has spread very rapidly which has led to the current pandemic. Secondary infections are reported now a days during the illness in Covid-19 patients of any age and patients recovered from COVID 19. The high-risk conditions prone for opportunistic infections are uncontrolled blood sugar levels, prolonged steroid usage and oxygen therapy. Mucormycosis is highly invasive secondary infection. Early diagnosis along with surgical and medical intervention and control of all risk factors plays a crucial role. Delay in presentation of patient to medical care is really challenging to the physicians and ENT surgeons.